Association of Ambient Air Pollution With Invasive Pulmonary Hemodynamics and Long‐Term Outcomes in Patients With Pulmonary Arterial Hypertension - Sicheng Zhang; Luyang Gao; Sicong Li; Manqing Luo; Qunying Xi; Ping Lin; Zhihui Zhao; Qing Zhao; Xiaoxu Xie; Qin Luo; Yansong Guo; Zhihong Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although the impact of ambient air pollution on mortality in cardiovascular and pulmonary diseases is well documented, its specific link to pulmonary arterial hypertension remains unclear. This study investigated the association between ambient particulate matter (PM) exposure and all‐cause death or lung transplantation, as well as pulmonary hemodynamics in patients with pulmonary arterial hypertension. Methods This retrospective cohort study included 1327 participants with pulmonary arterial hypertension who underwent right heart catheterization (RHC). Ambient PM2.5 and PM10 levels were estimated using the China High Air Pollutants data set, with a 3‐year average exposure before diagnosis as the primary exposure metric. All‐cause death or lung transplantation was the primary end point. Cox proportional hazard models assessed the association between PM exposure and primary outcomes, and generalized linear models evaluated pulmonary hemodynamics. Mediation analysis explored potential mediating factors. Results The median age of the participants was 33.0 years, with 73.2% being women. Median PM2.5 and PM10 levels were 58.0 [43.6‐76.1] and 103.0 [80.4‐129.3] μg/m3, respectively. Over a median follow‐up of 3.1 years, 149 patients died or underwent lung transplantation. Each 10 μg/m3 increase in PM2.5 and PM10 was associated with a 14.5% and 7.9% increased risk of primary outcomes, respectively. PM exposure was linked to worsened pulmonary hemodynamics, such as pulmonary vascular resistance and cardiac index. Mediation analysis suggested lipid metabolism, uric acid, and lymphocytes may partially mediate these effects. Conclusions Long‐term PM2.5 and PM10 exposure is not only associated with increased risk of death or lung transplantation in patients with pulmonary arterial hypertension but also affects disease severity and pulmonary hemodynamics.